2019
DOI: 10.1097/pec.0000000000001698
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, Management, and Outcome of Pediatric Epistaxis

Abstract: Objective: Epistaxis in children is one of the most common causes for seeking professional medical help. Patients may be treated by several disciplines with various approaches to pediatric epistaxis. We reviewed cases of pediatric epistaxis from an otorhinolaryngologist's point of view.Methods: A retrospective chart review was performed on all patients younger than 18 years presenting with epistaxis to the Department of Otorhinolaryngology at the University of Bonn, Germany.Results: Sixty episodes of epistaxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 30 publications
3
22
0
8
Order By: Relevance
“…A previous study reported that factors, such as chronic sinusitis, alcohol intake, and smoking, increase the risk of epistaxis in adults [ 11 ]. In children, epistaxis is seldom serious and is usually caused by digital trauma; it is largely self-limiting [ 25 ]. As children regularly attend school and engage in outdoor activities, environmental factors, such as weather and air conditions, have a greater influence on their health than on the health of adults [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that factors, such as chronic sinusitis, alcohol intake, and smoking, increase the risk of epistaxis in adults [ 11 ]. In children, epistaxis is seldom serious and is usually caused by digital trauma; it is largely self-limiting [ 25 ]. As children regularly attend school and engage in outdoor activities, environmental factors, such as weather and air conditions, have a greater influence on their health than on the health of adults [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies in the literature evaluating the causes and treatments of epistaxis in children. Most of these include examinations of specialties where patients are referred for further evaluation (5)(6)(7)(8). In other words, most of these patients are referred to these departments due to the need for further evaluation in primary care or emergency services.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these patients present to the emergency services due to the need for urgent medical intervention during or immediately after the bleeding, and the number of studies evaluating the cases who applied to the emergency department with epistaxis is very few (1,9). Many local such as digital trauma, sinusitis, rhinitis, mucosal dryness caused by nasal polyp or septum deviation, and systemic causes such as drugs, hypertension and coagulopathy are among the causes of epistaxis (6)(7). Although determining the etiology is important in planning and following the treatment; etiology varies according to the age of the patient and whether there is active bleeding (5,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic epistaxis may already occur in early childhood [4] and symptoms usually increase with age [5]. Unless treated in centers with experience in HHT, treatment is often limited to strategies applied in acute epistaxis [6].…”
Section: Introductionmentioning
confidence: 99%